Factors Influence of Purchase Intention on Beauty Product - Kusumawati, Marina; Rahmawan, Ginanjar (International Journal of Educational Research & Social Sciences, 2021)
Wardah is a brand of cosmetics in under the auspices of PT. Paragon Technology and Innovation. Wardah present as one of the brands of cosmetics the largest in Indonesia , products Wardah first time launched in the year 1995. PT. Paragon Technology and Innovation is always on top of market growth every year . Even Throughout the year 2020 Wardah has succeeded in exporting 22.9 billion worth to Malaysia. This study aims to determine the factors that influence the purchase interest of Wardah beauty products . The author will meniliti 4 factors such as Beauty Vlogger, Quality Products , Image Brand And price product it itself . The population in this study is the Consumer Products Beauty Wardah are domiciled in Soloraya include Boyolali , Karanganyar , Surakarta, Sukoharjo , Klaten , Sragen and Wonogiri . Research is using the technique of taking samples with a short a tan purposive sampling with the total respondents as many as 102 respondents . While for Technical analysis of the data using analysis regression linear multiple , Test T ( Partial ), Test F ( Simultaneous ) and Test Koefiesien of determination (R2). Based on the research that has been done, it can be concluded that this research according to the results of the partial T test, the variable that dominates the interest in purchasing wardah beauty products is the variable quality of the product where the product quality has a percentage value of 51.46% which is greater than the percentage value for the Beauty Vlogger variable. , Brand Image and Price.